Maturação de sementes de Poincianella Pluviosa (DC.) L. P. Queiroz (Sibipiruna): sementes tolerantes à dessecação e de baixa viabilidade no armazenamento - Silva, Joao Paulo Naldi [UNESP] (2014)
Seeds present different behaviors with respect to desiccation tolerance and storability after shedding, when a lower or switch-off metabolism provide greater success in storage. These behaviors can consist in categories that facilitate the use of techniques for conservation in germplasm banks, or even considered as a gradient among seeds of different species. A recent approach is that these different behaviors reside in the mature stage in which seeds are shed from the mother plant, being sensitive to desiccation seeds dispersed in a very immature stage. However, variations of the metabolism during maturation process and its consequences on seed viability after dispersion are still not well understood. The aim of this thesis was to evaluate the changes in the profile of the primary metabolism, carbohydrates and fatty acids during maturation and contextualize them to contribute to storability, using seeds of Poincianella pluviosa as model. The maturation period of these seeds is extensive and larger than its viability under environmental conditions. This process is characterized by a decrease of the primary energetic metabolism concomitant with the production of antioxidants via secondary metabolism and an accumulation of osmoprotectant compounds, wherein the last months of maturation are essential for large increase of seed vigor. These results were compared to seeds of Caesalpinia echinata, showing that low temperatures of storage increase these seeds storability, suggesting the presence of a reduced metabolism after dispersion. Both present antioxidant mechanisms, although not seem enough to control oxidation processes during storage. Differences on the extension of maturation between the two species can explain the storability of these seeds after shedding, when an advance in maturation would provide a greater reduction of primary energy metabolism